Study on the Attractiveness of Fruit Flies Bactrocera spp. to Mango Fruit’s Extract - Oka Dwi Handaru; Witjaksono Witjaksono; Edhi Martono (Jurnal Perlindungan Tanaman Indonesia, 2019)
Fruit fly (Bactrocera spp.) is a global major pest species of the fruit export and import activities. The controlling and monitoring strategies based on the ecology of fruit flies were expected to overcome the problem of fruit flies. The study on the attractant compound of fruit flies from mango extract  may provide an alternative to control and to monitor fruit flies, both male or female. This research was aimed to determine the strength of attractiveness (number and type of species) and durability (day) on mango extract which could attract fruit flies. The experiment was conducted in mango plantation in Sragen Regency using Randomized Complete Block Design (RCBD) with five different locations for setting up the trap, each location consisted of nine treatments. The parameter observations were the number of trapped-fruit flies, the sex of fruit flies, the type of species fruit flies, and the durability of mango extract. The results revealed that mango extract could attract the male and female fruit flies with mechanism through the presence of nutrition and oviposition site. Extract of raw Pakel mango had a good ability to attract fruit flies, either male or female of B. carambolae and B. papaya, and male of B. albistrigata with a total of 15 flies per trap in one week.